Slope Stability Analysis of Low Wall Pit 6 at PT Sarolangun Bara Prima, Mandiangin District, Sarolangun Regency, Jambi - Gary Aprio; Yoszi Mingsi Anaperta; Bambang Heriyadi; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2024)
PT Sarolangun Bara Prima is a company engaged in the coal mining industry located in Mandiangin sub-district, Sarolangun district, Jambi city. PT Sarolangun Bara Prima is one of the coal mining companies that uses open mining system with open-cut method. This research focuses on the Low Wall pit 6 slope of PT Sarolangun Bara Prima. from the results of field observations, the authors found water seepage and avalanches on the walls of the Low Wall pit 6 slope. The high rainfall at PT Sarolangun Bara Prima causes a decrease in the cohesion value and the value of the inner shear angle in the slope constituent material. The method used in analyzing the stability of the Low Wall Pit 6 slope is the Morgenstern-Price method which is run into slide 6.0 software. The analysis was carried out based on the actual slope section data in August 2023. from the results of the analysis of the stability of the Low Wall Pit 6 slope obtained a safety factor (FK) with a saturated state of 1.089 From the results of the analysis obtained, it explains that the Low Wall Pit 6 slope is in a keritis state. For this reason, the authors made modifications to the actual slope geometry to get FK ≥ 1.3 or the slope is said to be safe. The results of the modification of the geometry of the Low Wall pit 6 slope obtained FK value for saturated conditions is 1.30.